2020
DOI: 10.1002/acp.3646
|View full text |Cite
|
Sign up to set email alerts
|

Sketching while narrating as a tool to detect deceit

Abstract: In none of the deception studies that used drawings to date, was the effect of sketching on both speech content and drawing content examined, making it unclear what the full potential is of the use of drawings as a lie detection tool. A total of 122 truth tellers and liars took part in the study who did or did not sketch while narrating their allegedly experienced event. We formulated hypotheses about the total amount of information and number of complications reported and about various features of the drawing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 47 publications
(74 reference statements)
5
40
1
Order By: Relevance
“…This interview stage represents a typical deception experiment in which interviewees are interviewed once after the alleged event occurred. In such experiments, the MS and sketching while narrating techniques typically did result in the elicitation of extra information and cues to deceit (Vrij, Leal, Jupe, & Harvey, 2018; Vrij, Mann, et al, 2020). A possible explanation for the absence of a sketching effect is that participants were asked to report a sequence of actions similar to a film.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interview stage represents a typical deception experiment in which interviewees are interviewed once after the alleged event occurred. In such experiments, the MS and sketching while narrating techniques typically did result in the elicitation of extra information and cues to deceit (Vrij, Leal, Jupe, & Harvey, 2018; Vrij, Mann, et al, 2020). A possible explanation for the absence of a sketching effect is that participants were asked to report a sequence of actions similar to a film.…”
Section: Discussionmentioning
confidence: 99%
“…All verbal interviews were transcribed and coded separately for each session. The sketches were not coded, because previous research has shown that sketches made while narrating guide interviewees' verbal reports rather than act as stand‐alone lie detection tools (see Vrij, Mann, et al, 2020). Details were coded as PLATO details.…”
Section: Methodsmentioning
confidence: 99%
“…Interviewees may be asked to either sketch and then to narrate or to sketch while narrating Eastwood et al, 2019;Marlow & Hilbourne, 2011). Findings in the deception literature generally overlap for those two methods of introducing sketches and show that truth tellers provide more verbal details than lie tellers (Izotovas et al, 2020;Vrij et al, 2020). As truth tellers report an experienced event, whereas lie tellers fabricate at least some parts of the reported event, truth tellers' verbal reports of the event are likely to be richer than lie tellers' verbal reports (Amado et al, 2015).…”
Section: The Use Of Sketches To Elicit Information and Cues To Deceitmentioning
confidence: 98%
“…Further, sketching typically leads to the provision of spatial information as the interviewee must situate each person or object in a location on the sketch. In contrast, verbal reports do not require interviewees to spontaneously locate persons and objects (Vrij et al, 2020).…”
Section: The Use Of Sketches To Elicit Information and Cues To Deceitmentioning
confidence: 99%
See 1 more Smart Citation